The Impact of Green Marketing, Ecolabel Awareness, Green Brand Image, and Green Trust on Purchasing Decisions of AQUA Life Products - Dandi Kautsar; Mimin Aminah; Alim Setiawan Slamet (Universitas KH. Abdul Chalim Mojokerto, 2025)
The era of globalization is characterized by a very tight level of competition so that companies are required to have the ability to develop strategic choices in the field of marketing management and be able to adapt to the business environment. In an effort to win increasingly fierce competition, companies must be able to create marketing that suits the needs of consumers in modern society. Currently, there are many negative impacts on the environment due to consumption patterns and the rapid development of technology and the economy, resulting in the birth of many products that are not environmentally friendly. One of the causes is the large amount of plastic waste in the environment which has a negative impact on climate change, water and air pollution. The problem is, this increasing growth is not accompanied by poor processing of plastic bottle waste which will have an impact on environmental damage in the future because every year it increasingly accumulates and is not recycled. Therefore, it is necessary to carry out research which aims to analyze the influence of green marketing, ecolabel awareness, green brand image, and green trust on Aqua Life product purchasing decisions.